Protection of smart substation based on WLAN compliet with IEC 61850 using travelling wave analysis - Ali, Nasser Hasan (2017)
IEC 61850 is an important industry standard for substation automation. It is a suite of protocols that provides interoperability between different devices from different vendors in a substation environment. Among many other features, it has a unified application interface, unified model and provides seamless data access within the